EFFICACY OF SOME PROMISING WEEDICIDES ON SHALLOWLAND TRANSPLANTED RICE (ORYZA SATIVA L.) UNDER RAINFED CONDITIONS - PUNABATI HEISNAM; ABHINASH MOIRANTHEM; ANJU KEISHAM; N. INDRAKUMAR SINGH; A. HEROJIT SINGH; L. NABACHANDRA SINGH (The Bioscan, 2015)
An experiment was conducted at the Research Farm, College of Agriculture, Central Agricultural University,Imphal to study the efficacy of a 10 promising weedicides viz. Swat (Paraquat Dichloride 24% SL), Sunrice (Ethoxysulfuron 15% WDG), Topstar (Oxadiargyl 80% WP), Rice star (Fenoxoprop-P-ethyl 6.7% w/w EC), Sofit (Pretilachlor 30.7% w/w EC), Whipsuper (Fenoxoprop-P-ethyl 9.3% w/w), Champion (2,4-D Ethyl Ester 30% EC), Almix (Metsulfuron Methyl 10% + Chlorimum Ethyl 10%), Saathi (PyrazoSulfuron 50% EC) and Rifit (Pretilachlor 50% EC) under 11 treatments (including control treatment) in Randomized Block Design with 3 replications. Among the different herbicides tested T7 2,4-D Ethyl Ester 30% EC (Champion) was found better, during earlier growth stages upto 60 DAT, producing taller plants but at later stages T4 Fenoxoprop-P-ethyl 6.7 % w/w EC (Rice star) was found most effective to control weed least total weed biomass production (18.76g/m2 fresh weight and 8.67g/m2 dry weight), weed control efficiency (71.81%) and herbicide use efficiency (56.10 %). Different yield attributes viz. number of effective tillers per hill, number of spikelets, filled grains were recorded the highest with the application of Metsulfuron Methyl 10% + Chlorimum Ethyl 10% (Almix) weedicide T8 resulting to the highest grain yield (68.98 q/ha) increasing 20.29 % over control.